A relação entre estímulo partitural e resultado sonoro no script “Quatre Fois” de Didier Guigue - Brito, Luã Nóbrega de (2019)
This work of research has as its main objective to comprehend the piece Quatre Fois in a paradigm that considers the performance (and its implications) as fundamental. Its score (here seen as a script) can’t be read in solfeggio style, so it can’t have a directly tone output. That – at least at the beginning – is the reason for us to consider the performance-bound analytical approach as a viable solution. Therefore we are using the idea of Musical Morphology from Fiel da Costa (2016; 2017; 2018). Through this logic, we now see the script Quatre Fois as a stimulus which is animated by the performance process, that relation generates, then, an effect which its recurrence generates a morphological nexus, meaning that as a result of artistic nature, specially sonic. Analytically, all of those objects accrues from the performance process and their interactions are considered spots for analysis. Regarding our case, Quatre Fois, it was possible to study all the versions that were made and that we have notice of, from the year 1980 to 2018. The montages were made by 5 groups/individuals: the very composer of the piece, Didier Guigue (DG); the group whypatterns_ (WP); Valério Fiel da Costa and Matteo Ciacchi on the collective Artesanato Furioso (AF); and the American bassist Daniel Barbiero (DB). Using specific methodological tools, we could see from the montages of these groups the general morphology from the piece as an object of complex sonority, often noisy. The script ‘diverges to itself’ performance actions of which their formal schemes could give us a clue that they were essentially made by using the script contents. The great majority of the versions are long duration performances (>10 min) on which it is presented a five-section structure that each correlated sonority are specific and contrasting between themselves, each one representing a keyword contained in the script and also having a repetition of this whole five-section cycle for four times in a decreasing overall duration of each one. By identifying and understanding the role of the stimulus, it was also possible to discuss specific matters regarding the montages, whose data could be seen as a reflection of the context in which each one of the montages were inserted at the moment(s) that the versions was developed/played.